The Typological Position of The Languages of Nepal: Morphosyntax - Donohue, Mark; Kalyan, Siva (Nepalese Linguistics, 2024)
We examine the typological position of the languages of Nepal among the languages of the world, considering a broad sample of morphosyntactic features. Following a computational analysis, we find that: most of the languages of Nepal occupy a fringe position; some languages of Nepal lie outside the range of variation of other South Asian languages; and the languages of Nepal show correlations among morphosyntactic features that are not correlated globally.